MODEL OTONOMI DAERAH PADA MASA ORDE LAMA ORDE BARU DAN REFORMASI DI NEGARA KESATUAN REPUBLIK INDONESIA - Sagala, Andi; Firdaus, Emilda; Ghafur, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The area is a continuation of the central government in a unitary state, as implemented in Indonesia through the constitution which stipulates that the unitary state of Indonesia is divided into provincial regions and provincial regions divided into regencies and cities, and each province and district / the city has a local government. The regional administration based on the legislation that serves as the norm, strander, procedures, and judging is set by the central government.Law research method used is a normative legal research. Normative legal research refers to the legal norms contained in the legislation and judicial decisions. The nature of this research is descriptive research that is done is illustrate the results of these studies. Or the study of the principles of law, sestematika law, the degree of synchronization of law, legal history and comparative law.The application of legislation of local governments in development are constantly changing as well as policy implementation more decentralized continues to experience ups follow dynamics of incumbents, at least since the independence of Indonesia has had seven laws of local government, in three stages regime, namely the old regime, orde new, and order reforms. During the old order enacted Law No. 1 of 1945 and Act No. 22 In 1948, Law No. 1 In 1957, Law No. 18 In 1965, the new order of Law No. 5 of 1974, and at the time of the order of this reform since 1998 to date have been by the Law No. 22 of 1999 and Law No. 32 of 2004 where the laws no. 32 of 2004 have been revised four times, the first being revised by Law No. 8 In 2005, the latter was revised by Law No. 12 In 2008, the third through the law No. 23 of 2014 and the fourth through Act No. 9 of 2015. Based on studies that do against the law of local government, in any enforcement concept of the unitary state and the decentralization policy has always been the basis of its policies , although its implementation in local government there are regimes that have not fully is applying especially decentralization policies that can generate regional autonomy.Keywords: Autonomy, Mode, and the Unitary State.